Analysis of the Contribution of Marine Fisheries to Maritime Economic Growth in Indonesia - Moch. Barik Zulfikar; Setyo Wahyu Sulistyono (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2026)
This study aims to analyse the long-term and short-term relationships simultaneously. The data analysis method in this study uses the Vector Error Correction Model (VECM) between maritime GDP and three main indicators of the maritime economy, namely the number of fishermen, the fisheries sector, and the number of vessels, during the period 2014-2023 with monthly interpolation. The results show that in the long term, fishermen and capture fisheries have a significant effect on maritime GDP, while fishing vessels have no significant effect. Conversely, in the short term, no significant relationship was found between fishing vessels, capture fisheries, and maritime GDP.